The Persistence of the Accruals Anomaly* - Lev, Baruch; Nissim, Doron (Contemporary Accounting Research, 2006)
Abstract The accruals anomaly — the negative relationship between accounting accruals and subsequent stock returns — has been well documented in the academic and practitioner literatures for almost a decade. To the extent that this anomaly represents market inefficiency, one would expect sophisticated investors to learn about it and arbitrage the anomaly away. We show that the accruals anomaly still persists and, even more strikingly, its magnitude has not declined over time. How can this be explained? We show that the accruals anomaly is recognized and, indeed, exploited by certain active institutional investors, but the magnitude of this accruals‐related trading is rather small. By and large, institutions shy away from extreme‐accruals firms because their attributes, such as small size, low profitability, and high risk stand in stark contrast to those preferred by most institutions. Individual investors are also, by and large, unable to profit from trading on accruals information due to the high information and transaction costs associated with implementing a consistently profitable accruals strategy. Consequently, the accruals anomaly persists and will probably endure.